Gender in a ‘caring’ profession: The demographic and cultural dynamics of the feminisation of the probation service in England and Wales - Tidmarsh, Matt (Probation journal, 2024)
The number of women working in occupations that lay claim to professional status has increased markedly in recent decades, but the speed and extent of the ‘feminisation’ of the probation service in England and Wales render it unique. Such change has occurred against the backdrop of attempts to present the service in more ‘masculine’ terms, to increase punitiveness while maximising its efficiency. This article seeks to move explanations for feminisation beyond gender stereotypes about care work. Drawing on semi-structured interviews with 38 members of staff from across the probation estate, and with particular regard to the unification of services, it explores the demographic and cultural dynamics of feminisation. The article argues that the sustained (and ongoing) devaluation of probation's professional project, pay and working conditions have impacted retention and recruitment in such a way that has filtered into the gender composition of the service.